PENGARUH PERSEPSI RISIKO DAN EKSPEKTASI RETURN TERHADAP KEPUTUSAN INVESTASI DIGITAL PADA KALANGAN GENERASI Z - Yuningsih, Rahma; Windarti, Anissa; Nuraeni, Neng Sri (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2025)
Amid the rapid growth of digital investment platforms, Generation Z emerges as an active force exploring modern financial landscapes. Communities such as @Saham_fess on social media provide spaces to exchange insights and shape increasingly dynamic investment decisions. Engaging 112 Generation Z respondents under the age of 25, data were gathered through an online questionnaire and analyzed using multiple linear regression after passing validity, reliability, and classical assumption tests. The analysis reveals that expected return has a positive and significant effect on digital investment decisions, while risk perception shows no meaningful influence. These finding highlights that anticipated profit becomes a stronger consideration than perceived risk, reflecting a generation with relatively high-risk tolerance. These insights encourage digital investment service providers to emphasize not only potential returns but also to integrate stronger risk education for young investors.